COVID-19 reinfection in a patient with a serious mental illness within a long-term inpatient psychiatric care hospital - Brianna Englett, PharmD, BCPP; Amy Magdalany, PharmD; Tiffany L. Gordon, PharmD, BCPP; Kelly Holladay, PharmD, BCPP (American Association of Psychiatric Pharmacists, 2021)
There is an increasing number of case reports of COVID-19 reinfection. The mechanism of reinfection is poorly understood and evolving. Prevention of the transmission of severe acute respiratory syndrome coronavirus 2 for those with a serious mental illness (SMI) living in a congregate setting presents unique challenges. In this case report, we describe an individual with an SMI in a long-term inpatient psychiatric care hospital who was initially diagnosed in June 2020 with COVID-19 infection via a polymerase chain reaction test. Approximately 6 months later, the patient presented with a COVID-19 reinfection and more severe COVID-like symptoms.